2011
DOI: 10.1016/j.jcrysgro.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steady crucible rotation on the segregation of impurities in vertical Bridgman growth of multi-crystalline silicon

Abstract: a b s t r a c tWe have performed axisymmetric, transient simulations of the vertical Bridgman growth of multicrystalline (mc) silicon to study the effect of the steady crucible rotation on the melt flow and impurity segregation. A solute transport model has been applied to predict the final segregation pattern of impurities in a circular ingot. Imposing rotation rates of 1-5 rpm on the system makes radial segregation much worse compared to the non-rotating case. Low rotation rates at 1-2 rpm increase radial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…They showed that low rotation rates at 1–2 rpm increased the radial segregation in the first half period of solidification, while an opposite behavior was observed for the second half period of solidification. Here, radial segregation was increased at high rotation rates (from 3 to 5 rpm) with small impact at 1–2 rpm 31. The same group also studied the effect of the shape of the solidification front on the flow pattern and impurity distribution in mc silicon ingots 32.…”
Section: Improved Crystallization Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…They showed that low rotation rates at 1–2 rpm increased the radial segregation in the first half period of solidification, while an opposite behavior was observed for the second half period of solidification. Here, radial segregation was increased at high rotation rates (from 3 to 5 rpm) with small impact at 1–2 rpm 31. The same group also studied the effect of the shape of the solidification front on the flow pattern and impurity distribution in mc silicon ingots 32.…”
Section: Improved Crystallization Methodsmentioning
confidence: 98%
“…An extensive work in this direction has been done by the simulation group at SINTEF (a research center closely working with the university) and NTNU. Bellmann and Meese 31 have reported on the effect of the steady crucible rotation on the melt flow and impurity segregation. They showed that low rotation rates at 1–2 rpm increased the radial segregation in the first half period of solidification, while an opposite behavior was observed for the second half period of solidification.…”
Section: Improved Crystallization Methodsmentioning
confidence: 99%
“…In the crucible rotation around the 1–2 rpm, the first half of solidification obtains the maximum segregation in the radial direction and second half of the solidification, the radial direction obtained the minimum impurity segregation. [ 66 ] When the Si 3 N 4 coating is more in the silica crucible, then it reduces the oxygen dissolution in the melt which enhances the minority carrier lifetime. The Si 3 N 4 coating of 150–300 µm range gives better efficiency.…”
Section: Factors Involved In Chemical Reactionsmentioning
confidence: 99%
“…The 10 rpm crucible rotation maintains the uniform distribution of impurities. [ 66 ] The carbon concentration affects the equiaxed grain presence of the flat melt‐crystal interface. [ 81 ] The influence of an electromagnetic field affects the impurity concentration due to the convective flow, particularly for metallic impurities.…”
Section: Factors Involved In Chemical Reactionsmentioning
confidence: 99%
“…How to improve the quality of silicon ingots produced by the DS process is a widespread research focus, and many experiments or simulations were used to determine and optimize the transport phenomena in the DS furnace to understand and control the DS process parameters, including heat transfer, mass transfer, solid-liquid (s/l) interface shape, flow effect (including the argon flow in the furnace and silicon melt flow in the crucible) and the thermal stresses of the polysilicon during crystallization [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%